Thermodynamic study of the solubility of sodium sulfadiazine in some ethanol+ water cosolvent mixtures (2010)
Sodium sulfadiazine (SD-Na) is a drug extensively used for the treatment of certain infections caused by several kinds of microorganisms. Although SD-Na is widely used nowadays in therapeutics, the physicochemical information about their aqueous solutions